Molecular evidence for trans-stadial transmission of Anaplasma platys by Rhipicephalus sanguineus sensu lato under field conditions - Aktas, M.; Ozubek, S. (Wiley, 2018)
This study investigated the transmission of Anaplasma platys by Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae). Engorged nymphs (n = 404) removed from A. platys-infected dogs were incubated at 28 degrees C until moulting. Unfed adults were obtained and divided into 48 pools. Unfed ticks collected from the grounds of the dog shelter, comprising 1800 larvae (n = 18 pools), 3100 nymphs (n = 62 pools) and 85 adults (n = 10 pools, including three male and seven female pools) were sorted into 90 pools. All pools were screened by polymerase chain reaction for the 16S rRNA gene of A. platys. Of 48 pools of unfed adults obtained from engorged nymphs, 12 were positive for A. platys; the infection rate maximum likelihood estimate (MLE) was 3.36 [95% confidence interval (CI) 1.84-5.68]. Anaplasma platys was detected in five of 23 male pools (MLE 2.82, 95% CI 1.06-6.20) and seven of 25 female pools (MLE 3.83, 95% CI 1.72-7.57). Of seven pools of unfed adult females collected from the shelter grounds, one was positive for A. platys (MLE 1.74, 95% CI 0.11-8.22). Among 62 unfed nymph pools, eight were infected with A. platys (MLE 0.27, 95% CI 0.13-0.52). No A. platysDNA was detected in the larva pools. The present results reveal molecular evidence for the trans-stadial transmission of A. platys by R. sanguineus s.l.
Keywords: Anaplasma platys; Rhipicephalus sanguineus sensu lato; dog; trans-stadial transmission by R. sanguineus s.l.